Techno-Economic Analysis of Wind Energy Resources Based on Real Measurements in West Bank – Palestine - Ibrik, Imad H. (International Journal of Energy Economics and Policy, 2019)
The wind resource assessment in Palestine is one of the main issues necessary for achieving our renewable energy target in Palestine by 2025. In this paper, wind energy potential assessment of West Bank was investigated, focus on wind site assessment of using small wind turbine in different cities in West Bank. A wide variety of data types and analysis techniques will be presented, were utilized in performing the national wind energy assessments. Most of the data used in the assessments were collected at anemometer 10m heights and locations that chosen for wind energy assessment purposes, and many of these have been located in areas chosen by energy research centre thought to have high wind resource. The techno-economic analysis of collected wind data at different cities in West Bank also will be presented. Keywords: Wind resources assessment; Wind power density; Techno-economic Analysis. JEL Classification: Q4 DOI: https://doi.org/10.32479/ijeep.8067